Knowledge and Attitude regarding the Family Planning among Spouses in Sub-Urban Primary Health Care Centres in Erbil Province - Suzan Mustafa Muhammed; Tiran Jamil Piro (Erbil Journal of Nursing and Midwifery)
Background and Objectives: Family Planning refers to couples who make educated choices about having children, such as timing their pregnancies and limiting the number of children that they will have via contraceptive techniques. Objective of the Study: To assess couples' knowledge and attitudes about family planning and its association with their sociodemographic characteristics.